Assessment on the durability of chemically treated Gigantochloa Scortechinii in accelerated unsterile soil laboratory tests - Razak Wahab; Shafiqur Rahman; Othman Sulaiman; Mohd Sukhairi Mat Rasat (AENSI, 2013)
Cultivated 2 and 4 years old Gigantochloa scortechinii culms of internodes 6, 7, and 8, were chemically treated with ammoniacal-copper-quaternary (ACQ), borax-boric acid (BBA) and copper-chrome arsenate (CCA) at 1, 2, 4 and 8% concentrations respectively. Three different methods of chemical treatment were introduced to the bamboo through soaking, vacuum impregnation and high pressure sap-displacement process. An accelerated eight weeks laboratory unsterile soil burial tests were then carried out on the bamboo samples. At the completion of the testing period, the 2 year-old G. scortechinii were found to experience higher weight loss compared to the 4 year-old as the results of the attack by decay fungi. Comparison between the treatment processes showed that the vacuum pressure treated bamboos experienced lower weight loss. The 4% preservatives solution strength was found to be sufficient in controlling the decay fungi in the bamboos.